The portrayal of gender inequality in well-behaved Indian women novel by Saumya Dave - Faradita, Siti Hasyinah; Kusuma, Dwi Linda (Lililacs Journal, 2021)
This research aims to see how gender inequality is portrayed in the Well-Behaved Indian Women novel by Saumya Dave. Using the qualitative method and existentialist feminism approach by Simone de Beauvoir, this study will analyze the narration from the novel to see how the characters from this novel, Nandini and Simran, had to experience gender inequality and how they overcome it. The result of this study is that Nandini and Simran had to experience gender inequality in the form of unequal opportunity in their education, career, and relationship. They finally overcame the inequality and refused their otherness by having their opportunities and choosing what they thought was the best for them.